PERAN KESADARAN EKOLOGI DAN NORMA SOSIAL DALAM MENUMBUHKAN SOLIDARITAS SOSIAL SEBAGAI WUJUD CIVIC RESPONSIBILITY SISWA DI MA MIFTAHUN NAJAH - Najiatul Karimah; Nadiroh; Munawar Asikin; Achmad Husen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the role of ecological awareness and social norms in fostering social solidarity as a manifestation of civic responsibility in students at MA Miftahun Najah. Based on the theories of civic education and social learning, this qualitative case study employed in-depth interviews, participant observation, and documentation. The results indicate that the school's environmental program enhances collective awareness, while the internalization of social norms encourages cooperative action, forming social solidarity that becomes a practice of civic responsibility.